Bovine and goat milk fat globule membrane supplementation alleviates autism-like behavior by modulating lipid metabolism and gut microbiota - Rui Guo; Xiao Xiao; Chuanchuan Wang; Tian Yuan; Qianhui Zou; Tian Zhang; Jiarui Liang; Ying He; Zhuo Liu; Xuebo Liu; Shan Wu; Zhigang Liu (Food Science and Human Wellness)
Autism spectrum disorder (ASD) is a neurodevelopmental disorder influenced by genes and the environment. This study investigated the protective effects of bovine milk fat globule membrane (BMFGM) and goat milk fat globule membrane (GMFGM) supplementation on ASD model mice. Analysis of phospholipid composition showed higher levels of phosphatidylcholine in BMFGM and phosphatidylethanolamine in GMFGM. Behavioral results indicated MFGMs ameliorated social deficits, with GMFGM being more effective. Milk fat globule membrane (MFGM) mitigated neuroinflammation by suppressing microglial overactivation and proinflammatory cytokines expression, meanwhile GMFGM increased the anti-inflammatory factor interleukin (IL)-10. MFGMs also altered gut microbiota composition and maintained gut barrier integrity. Uniquely, GMFGM increased butyrate production. Correlation analysis revealed positive associations between social behavior, levels of phosphatidylcholine, sphingomyelin, and the abundance of Allobaculum, Clostridium_sensu_stricto, and Turicibacter. Overall, these findings revealed the protective effects of MFGMs on neurodevelopment in ASD animal models and the underlying mechanism could be partly explained by their regulation of gut microbiota by the phospholipid components in MFGM.